Optimal planning of piecewise quintic polynomial trajectories for parallel robots to pass through singularities - Ünsal, Cem Burak (My University, 2023)
Yörünge planlama, robotik alanındaki önemli araştırma konuları arasında yer almaktadır. Paralel robotlar için yörünge planlamasındaki kritik hususlardan biri, çalışma uzaylarının içinde aktüasyon tekilliklerinin bulunmasıdır. Bu tekillikler etrafında, yörünge tutarsızsa, ters dinamik çözümünün büyüklüğü sonsuza ıraksar. Tutarlı yörüngeler literatürde genellikle tek bir sekizinci dereceden polinom ile planlanır. Bununla birlikte, aynı amaçla alternatif olarak parçalı kuintik bir polinom kullanılabilir. Bu tezde, tekilliklerden geçen paralel robotlar için bir optimal parçalı kuintik polinom yörünge planlama yöntemi geliştirilmiştir. Geliştirilen yöntem, geçilecek tekillikte tutarlılık koşulunu sağlarken aynı zamanda robotun ileri-geri hareketini önlemek için kullanılabilir.

Trajectory planning is one of the important research topics in robotics. A critical issue in planning trajectories for parallel robots is the existence of actuation singularities inside their workspace. Around these singularities, the magnitude of the inverse dynamics solution diverges to infinity if the trajectory is inconsistent. Consistent trajectories are usually generated in the literature with a single eighth-degree polynomial. However, a piecewise quintic polynomial can alternatively be employed with the same aim. In this thesis, an optimal piecewise quintic polynomial trajectory planning method is developed for parallel robots passing through singularities. The developed method can be used for avoiding back-and-forth motion of the robot while satisfying the condition for consistency at the singularity to be passed through.
Paralel robotların tekilliklerden geçmesi için parçalı kuintik polinom yörüngelerin optimal planlaması
Keywords: Makine mühendisliği; Mechanical engineering; Paralel manipülatörler; Paralel robotlar; Parallel manipulators; Parallel robots; Robotics; Robotik; Singularity; Tekillik